Trace Element Speciation and Nutrient Distribution in Boerhavia elegans: Evaluation and Toxic Metal Concentration Across Plant Tissues - Tahreer M. Al-Raddadi; Lateefa A. Al-Khateeb; Mohammad W. Sadaka; Saleh O. Bahaffi (Toxics)
This study investigated the elemental composition of Boerhavia elegans, addressing the gap in comprehensive trace element profiling of this medicinal plant. The research aimed to determine the distribution of macronutrients, micronutrients, and beneficial and potentially toxic elements across different plant parts (seeds, leaves, stems, and roots). Using ICP-OES analysis, two digestion methods were employed to capture both complex and labile elements. The study revealed distinct elemental distribution patterns, with iron and nickel concentrating in stems, manganese and zinc in leaves, and copper in roots. Magnesium emerged as the most abundant macronutrient, particularly in leaves. Importantly, all detected toxic elements (arsenic, chromium, lead, and cadmium) were below WHO safety limits. These findings provide crucial insights into the nutritional and safety profile of B. elegans, potentially informing its use in traditional medicine and highlighting its potential as a source of essential elements.